Transforaminal Endoscopic Discectomy Under General and Local Anesthesia: A Single-Center Study - Kerimbayev, Talgat; Kenzhegulov, Yergen; Tuigynov, Zhandos; Aleinikov, Viktor; Urunbayev, Yermek; Makhambetov, Yerbol; Pan, Andrew; Abishev, Nurzhan; Oshayev, Meirzhan; Baiskhanova, Dinara; Solodovnikov, Makar; Akshulakov, Serik (Frontiers in Surgery, 2022)
Percutaneous spinal endoscopy is used for the treatment of disorders of the lumbar spine, as it has several advantages over traditional surgical methods. The performance of percutaneous spinal endoscopy is not possible without applying anesthesia methods. Two types (local and general) of anesthesia are used for percutaneous spinal endoscopy. Both, local and general anesthesia approaches contribute to safety in surgical procedures. Although it is believed that the method of local anesthesia has more benefits over general anesthesia, such as lowering the risk of postoperative neurological complications in a patient, the literature on the topic is inconclusive. The study aims to perform a comparative analysis of the two anesthesia methods using a prospective case-control design. Patients were divided into two groups: those who received local anesthesia (LA, 20 patients), and those who underwent general anesthesia (GA, 20 patients). As a result of the study, 40% of patients experienced moderate pain, and 5% of patients experienced excruciating pain intraoperatively in the LA group. Although VAS and ODI scores improved more rapidly in LA group, at the 12-month check-up point there was no significant difference between cases and controls. Nevertheless, there were postoperative complications such as nerve root injury in 10% of patients; nausea, vomiting, dizziness, drowsiness in 15% of patients in GA group, and insignificant or no such complications in patients of the LA group. The present study demonstrates that LA contributes to more positive short-term outcomes for patients as it facilitates nerve root damage prevention, and has no postoperative side effects on patients’ well-being.